Preclinical immune efficacy against SARS-CoV-2 beta B.1.351 variant by MVA-based vaccine candidates - Pérez, Patricia; Albericio, Guillermo; Astorgano, David; Flores, Sara; Sánchez-Corzo, Cristina; Sánchez-Cordón, Pedro J.; Luczkowiak, Joanna; Delgado, Rafael; Casasnovas, José M.; Esteban, Mariano; García-Arriaza, Juan (Frontiers in Immunology, 2023)
The constant appearance of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VoCs) has jeopardized the protective capacity of approved vaccines against coronavirus disease-19 (COVID-19). For this reason, the generation of new vaccine candidates adapted to the emerging VoCs is of special importance. Here, we developed an optimized COVID-19 vaccine candidate using the modified vaccinia virus Ankara (MVA) vector to express a full-length prefusion-stabilized SARS-CoV-2 spike (S) protein, containing 3 proline (3P) substitutions in the S protein derived from the beta (B.1.351) variant, termed MVA-S(3Pbeta). Preclinical evaluation of MVA-S(3Pbeta) in head-to-head comparison to the previously generated MVA-S(3P) vaccine candidate, expressing a full-length prefusion-stabilized Wuhan S protein (with also 3P substitutions), demonstrated that two intramuscular doses of both vaccine candidates fully protected transgenic K18-hACE2 mice from a lethal challenge with SARS-CoV-2 beta variant, reducing mRNA and infectious viral loads in the lungs and in bronchoalveolar lavages, decreasing lung histopathological lesions and levels of proinflammatory cytokines in the lungs. Vaccination also elicited high titers of anti-S Th1-biased IgGs and neutralizing antibodies against ancestral SARS-CoV-2 Wuhan strain and VoCs alpha, beta, gamma, delta, and omicron. In addition, similar systemic and local SARS-CoV-2 S-specific CD4+ and CD8+ T-cell immune responses were elicited by both vaccine candidates after a single intranasal immunization in C57BL/6 mice. These preclinical data support clinical evaluation of MVA-S(3Pbeta) and MVA-S(3P), to explore whether they can diversify and potentially increase recognition and protection of SARS-CoV-2 VoCs.